PENGARUH KEEFEKTIFAN PENGENDALIAN INTERNAL, ASIMETRI INFORMASI, KESESUAIAN KOMPENSASI DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Kasus pada OPD Kabupaten Kendal): Dibuat oleh Lilik,Sobrotul Imtikhanah, Tutut Dwi Andayani, Ferlinda Ainur Rachmani - Andayani, Tutut Dwi; Nur Indah, Lilik; Imtikhanah, Sobrotul; Ainur, Ferlinda (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
This study aims to test the effectiveness of internal control, information asymmetry, suitability of compensation and compliance of accounting rules against tendencies of accounting fraud. This study used quantitative methods with primary data obtained directly from respondents’s answer to questionnaries. The population in this study is all the authorities and responsible for the use of budgeted fubds, accounting implementes and people whose duties are related to the preparation of financial statements and accountability reports ini OPD Kendal Regency. This study used purposive sampling method with 66 respondents as the sample. The data analysis method used in this study was multiple linear regression analysis with IBM SPSS Statistics 21. The results of this research showed that (1) The effectiveness of internal control has a significant effect on the tendency of accounting fraud, (2) Information asymmetry has a significant effect on the tendency of accounting fraud, (3) The suitability of compensation has no significant effect on the tendency of accounting fraud, (4) Compliance of accounting rules has no significant effect on the tendency of accounting fraud, (5) Effectiveness of internal control, information asymmetry, the suitability of compensation and the observance of accounting rules simultaneously have a significant effect on the tendency of accounting fraud.